SEMIOTIKA ROLAND BARTHES: REPRESENTASI DINAMIKA SOSIAL FILM TILIK SUTRADARA WAHYU AGUNG PRASETYO - Surya Darma; Dani Manesah; Giovani; Triadi Sya’Dian; Sri Wahyuni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study explores the representation of social dynamics in the film Tilik (2018) by Wahyu Agung Prasetyo using the semiotic approach of Roland Barthes. In this research, a qualitative descriptive-analytical method is employed to identify and interpret visual and verbal signs. Three layers of meaning—denotation, connotation, and myth—are used in the analysis. The results show that the film Tilik portrays the social dynamics of rural communities, particularly interactions among women. These interactions are characterized by prevailing cultural norms, constructions of social status, and the practice of gossip. At the denotative level, the film depicts the everyday activities of village communities, while at the connotative level, it reveals social jealousy, social control, and gender stereotypes. At the level of myth, the film constructs collective values such as the importance of maintaining women's dignity, strong social solidarity, and the legitimization of gossip as a means of regulating social norms. Therefore, the film Tilik not only reflects social reality but also conveys deeper cultural meanings. Keywords: Semiotics, Roland Barthes, Social Dynamics, Film, Cultural Representation   Abstrak: Studi ini mengeksplorasi representasi dinamika sosial dalam film Tilik (2018) oleh Wahyu Agung Prasetyo menggunakan pendekatan semiotika Roland Barthes. Dalam penelitian ini, metode deskriptif-analitis kualitatif digunakan untuk mengidentifikasi dan menafsirkan tanda visual dan verbal. Tiga lapisan makna—denotasi, konotasi, dan mitos—digunakan untuk melakukan analisis. Hasil penelitian menunjukkan bahwa film Tilik menunjukkan dinamika sosial masyarakat pedesaan, terutama interaksi antarperempuan. Norma budaya yang berkembang, konstruksi status sosial, dan praktik gosip menandai interaksi ini. Dalam film, aktivitas sehari-hari masyarakat desa diungkapkan pada tingkat denotatif, sedangkan kecemburuan sosial, kontrol sosial, dan stereotip gender diungkapkan pada tingkat konotatif. Mitos menciptakan nilai kolektif seperti pentingnya mempertahankan martabat perempuan, solidaritas sosial yang kuat, dan legitimasi gosip sebagai cara untuk mengontrol norma. Akibatnya, film Tilik menunjukkan realitas sosial dan memiliki makna kultural. Kata Kunci: Semiotika, Roland Barthes, Dinamika Sosial, Film, Representasi Budaya